Seismic rotational stability of gravity retaining walls by modified pseudo-dynamic method. Issue 94 (March 2017) - Pain, Anindya; Choudhury, Deepankar; Bhattacharyya, S K
Abstracts: Seismic stability analysis is an important aspect for design of safe retaining walls in earthquake prone areas. In this study, limit equilibrium method is used for rotational stability analysis of gravity retaining wall on rigid foundation supporting dry cohesionless backfill with modified pseudo-dynamic seismic forces. Proposed method satisfies the zero stress boundary condition at free ground surface and considers the amplification of acceleration. Stability factor F W is proposed to determine the safe weight of the retaining wall against rotational failure under seismic conditions. If the safe weight of the retaining wall is known under static condition then by simply multiplying that with F W can give the safe weight of the retaining wall against rotational failure under seismic condition. Present study shows that wall-soil interaction in various seismic conditions may or may not be in-phase for the entire duration of the input motion. It depends on the properties of the backfill soil, properties of the wall material and also on the frequency content of the input motion. A modified rotating block method is proposed to obtain the rotational displacement under seismic conditions. Present results give higher values of rotational displacements of the wall when compared with the available results by pseudo-static analysis. Hence the present study may be used to design seismically stable retaining wall. Highlights: Modified pseudodynamic method satisfies boundary conditions Amplification of acceleration is inherent to soil properties Seismic active earth thrust and its point of application for gravity retaining wall Seismic stability factors for retaining wall against rotational mode of failure Rotational displacement of gravity retaining wall under seismic conditions